Trigo y cebada : costos y rentabilidad en la campaña 2025/2026 - Carrasco, María Soledad; De Leo, Geronimo; Conti, Veronica Andrea (Estación Experimental Agropecuaria Bordenave, INTA, 2025)
EEA Bordenave